Identification of Forest Bathing (Shinrin-Yoku) Tourism Routes in The Tahura Bunder Area, Gunung Kidul, Special Region of Yogyakarta - Afif, Fuadi; Mahiswara, Amelia Lintang (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
Some people are starting to complain about and experience physical and mental health issues as a result of living in cities and using electronic devices. Going back to nature is one way to lessen these issues. Forest bathing is one method of getting back to nature. Finding the forest bathing routes in Tahura Bunder, Yogyakarta, is the goal of this study. This study employed a qualitative method. In order to verify the data that had been gathered, additional measuring tools and literature reviews were used in addition to on-site research to conduct direct research. Tahura Bunder is a great place to take a forest bath, according to the study findings. Following that, three route models—the novice route, the intermediate route, and the expert route—were produced from the identification of routes on Tahura Bunder. The components that should be present in these three paths can be measured and observed to determine which ones they are. The study concludes that Tahura Bunder is a great place for forest bathing, offering three different routes for visitors to choose from as a potential health tourism activity.